2007
DOI: 10.1001/archderm.143.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Store-and-Forward Teledermatology in Skin Cancer Triage

Abstract: To evaluate a store-and-forward teledermatology system aimed at the routine triage of patients with skin cancer.Design: A multicenter, longitudinal, 4-phase, descriptive and evaluation study of a referred sample of patients attended through teleconsultation between March 2004 and July 2005. Clinical and dermoscopical examination and histopathological study were considered the gold standard.Setting: A skin cancer unit of a public university hospital and 12 primary care centers in southern Spain. Patients:The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(43 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…The time intervals to diagnosis and to treatment of skin cancers provide a convenient, yet objective, measure to assess management by teledermatology since clinical diagnoses are usually confirmed unambiguously by histology of a biopsy specimen, and surgical intervention constitutes a definitive therapeutic end point, and delays in diagnosis and treatment can potentially lead to increased morbidity. 21 Consistent with previous reports that S/F teledermatology facilitates triage of skin cancer patients, 16,20 our results indicate that remote patients with skin cancers or suspected skin cancers were initially evaluated more quickly when referred via teledermatology as compared to conventional clinicbased referrals. Importantly, the overall results also demonstrate that diagnosis by biopsy and definitive treatment also occurred earlier with teledermatology than with conventional consultation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The time intervals to diagnosis and to treatment of skin cancers provide a convenient, yet objective, measure to assess management by teledermatology since clinical diagnoses are usually confirmed unambiguously by histology of a biopsy specimen, and surgical intervention constitutes a definitive therapeutic end point, and delays in diagnosis and treatment can potentially lead to increased morbidity. 21 Consistent with previous reports that S/F teledermatology facilitates triage of skin cancer patients, 16,20 our results indicate that remote patients with skin cancers or suspected skin cancers were initially evaluated more quickly when referred via teledermatology as compared to conventional clinicbased referrals. Importantly, the overall results also demonstrate that diagnosis by biopsy and definitive treatment also occurred earlier with teledermatology than with conventional consultation.…”
Section: Discussionsupporting
confidence: 90%
“…3,4 Other clinical end points have also been examined, including patient satisfaction, [5][6][7][8][9][10][11] concordance in recommendations for management including biopsy, [11][12][13][14] and time to initial intervention. 11,[15][16][17] Beyond these surrogate or intermediate end points, however, few studies have addressed whether S/F teledermatology in actual practice affects the ultimate clinical outcomes or resolution of a dermatologic problem, Abbreviations used:…”
Section: Introductionmentioning
confidence: 99%
“…10 The other studies had more than one teledermatologist. [14][15][16][17][18][19][20][21] Of the four studies, measuring inter-observational agreement for in-person exams, two showed significantly better agreement among in-person clinicians than distant teledermatologists, 11,12 especially for primary diagnoses, and two did not. 10,13 A PubMed search for teledermatology research done after the latest research reviews published in 2011 9 identified only one additional study having two in-person dermatologists.…”
Section: Introductionmentioning
confidence: 94%
“…In-person agreement is reported in only four, [12][13][14][15][16] however, one of which 13 appears to be a pilot for another. 10 The other studies had more than one teledermatologist.…”
Section: Introductionmentioning
confidence: 94%
“…For example, in a study of Spanish patients attending a pigmented lesion clinic, the sensitivity for the detection of malignant versus benign tumors by teledermatology was 0.99 (95% CI, 0.98-1.00) while specificity was 0.62 (95% CI, 0.56-0.69). 19 Further research into which conditions are better suited for teledermatology consultation, and mobile teledermatology in particular, is warranted.…”
Section: Discussionmentioning
confidence: 99%